2012
DOI: 10.1108/17449201211277174
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol problems in a remand Scottish prisoner population

Abstract: This is the first study to focus solely on a remand prisoner population and the results show high levels of need. The criminal justice setting is ideally placed to identify and treat alcohol problems in this hard to reach population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
0
15
1
Order By: Relevance
“…Furthermore, majority of the participants in this study were Orthodox-Christian followers in which drinking alcohol is not prohibited by the religion. On the other hand, the prevalence of AUD in our study is lower than some of the previous studies which reported prevalence ranging from 69.3 to 73.0% [11,34,42]. This variation may be due to several reasons, including differences in socio-cultural, economic, and living conditions.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, majority of the participants in this study were Orthodox-Christian followers in which drinking alcohol is not prohibited by the religion. On the other hand, the prevalence of AUD in our study is lower than some of the previous studies which reported prevalence ranging from 69.3 to 73.0% [11,34,42]. This variation may be due to several reasons, including differences in socio-cultural, economic, and living conditions.…”
Section: Discussioncontrasting
confidence: 83%
“…On the other hand, the prevalence of substance use disorder (SUD) among prisoners before imprisonment was higher than both from use in prison and use in the general population, which may indicate association between crime and substance use. Studies in prisoners have shown that prevalence ranged from 50 to 88% for general substance use and 13 to 86% for AUD before imprisonment [11,12,16,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. A recent systematic review of about 24 studies from 10 different countries reported prevalence of AUD ranging from 16 to 51% among newly incarcerated male prisoners, with a pooled prevalence of 26% [46].…”
Section: Introductionmentioning
confidence: 99%
“…First, hazardous and harmful alcohol consumption is often stigmatized, potentially increasing the rates of refusal to participate. Second, problematic alcohol consumption may be associated with a higher likelihood of selective exclusion from the sampling frame—for instance, through homelessness ( 42 ) or incarceration ( 43 ). Third, hazardous and harmful drinking may decrease the likelihood of survey administrators being able to contact potential respondents, even when they remain in the sampling frame.…”
Section: Discussionmentioning
confidence: 99%
“… 7 The need for ABIs to be tailored specifically for the prison population is warranted to ensure they are relevant and acceptable to male remand prisoners. 8 A recent literature review of prison-based interventions identified 28 studies between 1995 and 2009. These were largely based in the USA with a focus on young offenders and women, 9 of which only one related to ABIs and targeted women prisoners.…”
Section: Introductionmentioning
confidence: 99%